2013
DOI: 10.1097/cnq.0b013e3182750acd
|View full text |Cite
|
Sign up to set email alerts
|

Building a Protocol to Guide Mobility in the ICU

Abstract: Professional experience and wisdom have taught us that immobility is a risk factor for various adverse outcomes, such as deep vein thrombosis, joint contractures, pulmonary dysfunction, and bone demineralization to name a few. Balancing bed rest and mobility may improve both short- and long-term outcomes for our patients. Moreover, early, routine mobilization of critically ill patients is safe and reduces hospital length of stay, shortens the duration of mechanical ventilation, improves muscle strength, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
0
26
0
6
Order By: Relevance
“…54 Physical therapy has shown to be feasible, safe, even in the most complicated patients receiving the most advanced medical therapies (e.g., continuous renal replacement therapy, extracorporeal cardiopulmonary support). 62,63 Early activity can be done without increases in usual ICU staffing and with a low risk (<1%) of complications. 64 Studying patients early in the their course of mechanical ventilation (<3 days), Schweickert et al showed that a daily SAT combined with physical and occupational therapy, versus SAT alone, resulted in an improved return to independent functional status at hospital discharge, shorter duration of ICU-delirium, higher survival, and more days breathing without assistance.…”
Section: E: Early Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…54 Physical therapy has shown to be feasible, safe, even in the most complicated patients receiving the most advanced medical therapies (e.g., continuous renal replacement therapy, extracorporeal cardiopulmonary support). 62,63 Early activity can be done without increases in usual ICU staffing and with a low risk (<1%) of complications. 64 Studying patients early in the their course of mechanical ventilation (<3 days), Schweickert et al showed that a daily SAT combined with physical and occupational therapy, versus SAT alone, resulted in an improved return to independent functional status at hospital discharge, shorter duration of ICU-delirium, higher survival, and more days breathing without assistance.…”
Section: E: Early Mobilitymentioning
confidence: 99%
“…The close collaboration and coordination with medicine, nursing, and physical therapists is fundamental for an efficacy and safe strategy. 62 This is particularly important because the burden of illness affects not only the patient but his or her family or other caregivers as well. 54 …”
Section: E: Early Mobilitymentioning
confidence: 99%
“…On the basis of this literature review, an early mobility protocol 15 was developed and then further refined for use in patients with burns. "Bed rest" was frequently used as a standard order postoperatively and on admission for all patients.…”
Section: Strategies To Overcome Barriers To Mobilizationmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] In 2007, Morris and colleagues evaluated the feasibility, safety, and outcomes associated with a ''mobility team.'' Seven days per week, a physical therapist, critical care nurse, and nursing assistant utilized a protocol for mobilization and criteria for limiting therapy.…”
mentioning
confidence: 99%